Penerapan Media Audio Murottal Untuk Meningkatkan Hafalan Al-Qur’an Siswa Kelas 5 di MI Ma’arif NU 01 Tunjungmuli Kecamatan Karangmoncol Kabupaten Purbalingga Tahun Pelajaran 2023/2024 - Muntofingah Muntofingah; Robingun Suyud El Syam; Nasokah Nasokah (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
In this thesis research, the author uses descriptive research with a qualitative approach, where this research is field research. The data collection technique used in this research uses observation, interviews and documentation methods. This thesis aims to: 1) To determine the process of implementing murottal audio media in memorizing the al-Qur'an for grade 5 students at MIMA NU 01 Tunjungmuli; 2) To find out how the use of murottal audio media can help improve the memorization of the al-Qur'an for grade 5 students at MIMA NU 01 Tunjungmuli; 3) To find out the obstacles in memorizing the al-Qur'an through audio murottal media for class 5 students at MIMA NU 01 Tunjungmuli. The results of this research show that the process of learning to memorize the al-Qur'an is carried out three times a week from 07:00 to 08:00 WIB and begins with the practice of dhuha prayers, reciting asmaul husna, and praise. followed by muroja'ah together and increasing the memorization of the al-Qur’an by listening to murottal from Ustadz Bilal Attaki. The use of this media has provided increased results as evidenced by the quality of students' memorization which is getting better and their recitation is being maintained. Most of the students have also achieved the target for memorizing the al-Qur’an set by the school. Apart from that, the application of murottal audio media cannot be separated from supporting and inhibiting factors. Supporting factors in memorizing the Qur'an using murottal audio media are the students' intention and enthusiasm in memorizing and practicing muroja'ah as well as the role and support of teachers and parents. Meanwhile, the inhibiting factors are the lack of tahfidz teachers, lack of learning time, sudden power outages, and students' feelings of laziness.